Effects of leptin on proliferation of astrocyte- and tanycyte-like neural stem cells in the adult mouse medulla oblongata. (December 2021) - Nambu, Yuri; Ohira, Koji; Morita, Mitsuhiro; Yasumoto, Hiroki; Kurganov, Erkin; Miyata, Seiji
Graphical abstract: Highlights: Stable neurospheres were generated from the adult mouse area postrema and central canal. Astrocyte-like neural stem cells in the area postrema actively proliferated. Tanycyte-like neural stem cells in the central canal were quiescent. Leptin receptors were expressed at astrocyte-like neural stem cells. Leptin promoted the growth of astrocyte-like neural stem cells in vitro and in vivo . Abstract: Astrocyte- and tanycyte-like neural stem cells (NSCs) were recently detected in the area postrema (AP) and central canal (CC) of the adult medulla oblongata, respectively. The present study aimed to examine dynamical behaviors of the astrocyte- and tanycyte-like NSCs of the mouse medulla oblongata to leptin. The neurosphere assay identified astrocytes in the AP and tanycytes in the CC as NSCs based on their self-renewing neurospherogenic potential. Both NSCs in neurosphere cultures were multipotent cells that generate astrocytes, oligodendrocytes, and neurons. Astrocyte-like NSCs actively proliferated and tanycyte-like NSCs were quiescent under physiologically-relevant in vivo conditions. Chronic leptin treatment promoted proliferation of astrocyte-like NSCs in the AP both in vitro and in vivo . Leptin receptors were expressed in astrocyte-like, but not tanycyte-like NSCs. Food deprivation significantly diminished proliferation of astrocyte-like NSCs. Therefore, the present study indicates that proliferation of astrocyte-like, but not tanycyte-like NSCs is regulated by nutritional conditions.